2018
DOI: 10.1051/0004-6361/201833285
|View full text |Cite
|
Sign up to set email alerts
|

Highly accreting quasars: The SDSS low-redshift catalog

Abstract: Context. The most highly accreting quasars are of special interest in studies of the physics of active galactic nuclei (AGNs) and host galaxy evolution. Quasars accreting at high rates (L/L Edd ∼ 1) hold promise for use as 'standard candles': distance indicators detectable at very high redshift. However, their observational properties are still largely unknown. Aims. We seek to identify a significant number of extreme accretors. A large sample can clarify the main properties of quasars radiating near L/L Edd ∼… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 98 publications
3
81
0
Order By: Relevance
“…A similar effect was found in quasars at both low and high redshifts (e.g. Negrete et al 2018;Vietri et al 2018). However, as far as we know, this is the first time that the correlation is found for a blazar.…”
Section: Blueshifts and Outflow Propertiessupporting
confidence: 82%
“…A similar effect was found in quasars at both low and high redshifts (e.g. Negrete et al 2018;Vietri et al 2018). However, as far as we know, this is the first time that the correlation is found for a blazar.…”
Section: Blueshifts and Outflow Propertiessupporting
confidence: 82%
“…An elementary error budget suggests that the main uncertainty is associated with FWHM measurement errors and with uncertainty in the structure factor (Marziani and Sulentic, 2014a;Negrete et al, 2018). The broad profile of both LILs and HILs in each quasar spectrum can be modeled by considering two main components, the Hβ BC and the blueshifted component BLUE ( §2).…”
Section: Discussionmentioning
confidence: 99%
“…Vetting the sample on strongest FeII and weakest [OIII]λλ4959,5007 emitters reduces the scatter but only slightly . Negrete et al (2018) have convincingly shown that orientation effects are at the origin of a large fraction of the scatter if lines are emitted in a flattened system (κ 0.2). The difference between virial and concordance luminosity estimates can be zeroed if the structure factor is assumed to be dependent on angle θ in the form given by Eq.…”
Section: Refer Tomentioning
confidence: 97%
See 2 more Smart Citations